2013
DOI: 10.1128/jvi.01189-13
|View full text |Cite|
|
Sign up to set email alerts
|

BK Polyomavirus Genotypes Represent Distinct Serotypes with Distinct Entry Tropism

Abstract: BK polyomavirus (BKV) causes significant urinary tract pathogenesis in immunosuppressed individuals, including kidney and bone marrow transplant recipients. It is currently unclear whether BKV-neutralizing antibodies can moderate or prevent BKV disease. We developed reporter pseudoviruses based on seven divergent BKV isolates and performed neutralization assays on sera from healthy human subjects. The results demonstrate that BKV genotypes I, II, III, and IV are fully distinct serotypes. While nearly all healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 41 publications
6
86
0
Order By: Relevance
“…The criterion used to designate serotypes is generally based upon a fold difference in antibody-mediated neutralization titers between viral types, which differ in magnitude and range between virus families: for adenovirus, 8-to 16-fold (52); for rotavirus, Ն20-fold (53); and for polyomavirus, 4-to 100-fold (54). For HPV there are no currently defined criteria with which to designate L1 serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The criterion used to designate serotypes is generally based upon a fold difference in antibody-mediated neutralization titers between viral types, which differ in magnitude and range between virus families: for adenovirus, 8-to 16-fold (52); for rotavirus, Ն20-fold (53); and for polyomavirus, 4-to 100-fold (54). For HPV there are no currently defined criteria with which to designate L1 serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…BKPyV persists in the urinary tract of the individual and is shed in the urine asymptomatically. BKPyV exists in 4 genotypes (I-IV) and subtypes, which are distinguishable by neutralization serology (Pastrana et al 2013). Subtype Ia is thought to be the most prevalent subtype and is prevalent worldwide, and subtype IV is less common and its prevalence appears to vary in different world regions Jin 1993;Takasaka et al 2004).…”
Section: Bkpyvmentioning
confidence: 99%
“…Studies based on virus-like particle (VLP)-based neutralizing assays indicated that VP1 capsid proteins of each of the major BKPyV genotypes can reciprocally escape from neutralization by antibodies raised against the other types. These serotypedefining differences between the genotypes can be related to a few key amino acid differences within the VP1-BC2 surface loop (Pastrana et al 2013). Based on cellbased transduction assays, this study also indicated that different BKPyV genotypes and subtypes may have altered attachment requirements and virulence potential in vivo, reflecting the changes in amino acids within their VP1 capsomere knob (Pastrana et al 2013).…”
Section: Receptors and Coreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many viral surface antigens have the ability to selfassemble into VLPs that resemble the native viral particles in appearance, for example, in case of Human Papillomavirus (Kemp et al, 2011;Schiller and Muller, 2015), JC polyomavirus (Ray et al, 2015), BK polyomavirus (Pastrana et al, 2013) etc. Many others that cannot self-assemble, or those where the viral capsid is encased inside a lipid envelope, or those where the viral surface proteins are relatively mobile/ not rigid, can also potentially be displayed in a more rigid and thermodynamically stable fashion as synthetic VLPs.…”
Section: Synthetic Vlpsmentioning
confidence: 99%